Notes on the presence of Manta alfredi in the Tubbataha Reefs natural Park, Cagayancillo, Palawan, Philippines - Aquino, Ma. Theresa R. (The Palawan Scientist, 2015)
In 2011, a review of 33 photographs of mantas taken at the Tubbataha Reefs Natural Park (TRNP), Cagayancillo, Palawan, Philippines revealed that most of the mantas photographed were clearly reef manta rays (Manta alfredi) with only one photograph of Manta birostris. Previously identified in surveys within the park as oceanic manta ray M. birostris, the presence of M. alfredi has never been established until now. Using various parameters, the pictures in the Tubbataha Management Office (TMO) database were reviewed and noted. The identification of M. alfredi was more consistently based on the presence of black marks located posterolateral to the last gill slits and between the rows of gill slits. The identification of the species was further validated by experts after viewing three photographs from the said database. This represents a new elasmobranch species record for the TRNP and, technically, for the Philippines as well. Furthermore, the confirmed presence of both globally significant species of manta rays should have a strong bearing on the conservation policies of the park as well as that of the country. Further research on population dynamics, structure and abundance is recommended. Contributing to global efforts to generate better understanding of the species through partnership with international organizations is also recommended.